Drug allergies and drug hypersensitivity reactions - Bozoglan, Merve Yilmaz (Nova Science Publishers, Inc., 2024)
Drug allergies and hypersensitivity reactions are increasing all over the world and are important reasons for post-marketing withdrawal of drugs, as well as clinically important for patients. Both hypersensitivity and allergic reactions account for 15% of all adverse drug reactions. The clinical manifestations of drug hypersensitivity reactions range from a simple rash to serious findings affecting internal organs. A lifethreatening reaction, anaphylaxis, especially due to beta-lactams, should be diagnosed and immediate treatment should be applied. The diagnosis of drug hypersensitivity reaction is based on history, clinical signs, and in-vivo and in-vitro biological tests. The attention of physicians will contribute to the prevention of false allergy diagnoses. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Anaphylaxis; Beta lactams; Drug allergy; Drug hypersensitivity reaction; Urticaria